PENGEMBANGAN PEMBIASAAN MEMBACA AL-QUR’AN DALAM MENANAMKAN KARAKTER ISLAMI PADA SISWA DI MA SITI FATIMAH PANDAAN - Charisma Auliya Firdaus; Saifulah Saifulah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This qualitative case study at MA Siti Fatimah Pandaan investigates how Qur'an reading habituation fosters Islamic character in students, addressing prevalent moral issues among Indonesian youth. The research posits that Islamic education, particularly through Qur'an reading, shapes character based on faith, Islamic law, and noble morals.Data gathered via observation, interviews, and documentation reveal that daily morning Qur'an reading sessions, held after Duha prayer and before classes, are guided by class teachers. This practice not only enhances students' Qur'an reading proficiency (including tajweed) but also significantly develops Islamic character. Positive outcomes include improved discipline, responsibility, and togetherness, alongside heightened spiritual awareness and moral conduct. The habituation helps students overcome reluctance to learn recitation and fosters a deeper connection to the Qur'an as a life guide. In conclusion, implementing Qur'an reading habituation at MA Siti Fatimah Pandaan effectively instills Islamic character, notably discipline, responsibility, and togetherness, while also boosting reading skills. The study recommends program continuation, student internalization of Qur'anic values, and its use as a future research reference.